Caractéristiques disciplinaires et échanges en santé au travail : perception et point de vue des chercheurs - Monique Lortie; Denys Denis; Claire Lapointe; Francine Mayer; Henriette Bilodeau (Perspectives Interdisciplinaires sur le Travail et la Santé)
This paper proposes reflection on the exchanges between researchers from different disciplines during collaboration in multi- and inter-disciplinary occupational health research projects, in particular regarding the role of disciplinary characteristics (insertion potential, permeability, flexibility, impacts/objectives) on the exchange process (object, ways of exchanging, costs, difficulties). In order to feed this reflection, 20 researchers were interviewed (closed and open questions). The results presented relate to the researchers’ perception of : their own discipline, their collaborators’ discipline, the level of exchanges (knowledge, methods, perspective, analyses), the resulting costs of these exchanges, the sources of difficulties and satisfaction, as well as the conditions that promote exchanges. The role of disciplinary characteristics and its potential impact is discussed, as well as the practical implications of some of the results.